2020
DOI: 10.1093/hmg/ddaa030
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide assessment of genetic risk for systemic lupus erythematosus and disease severity

Abstract: Using three European and two Chinese genome-wide association studies (GWAS), we investigated the performance of genetic risk scores (GRSs) for predicting the susceptibility and severity of systemic lupus erythematosus (SLE), using renal disease as a proxy for severity. We used four GWASs to test the performance of GRS both cross validating within the European population and between European and Chinese populations. The performance of GRS in SLE risk prediction was evaluated by receiver operating characteristic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 44 publications
5
56
1
Order By: Relevance
“…Genetic information may also be used to predict how severe the disease will be and identify patients that have an increased risk for certain organ manifestations. The genetic information can be leveraged by the use of polygenetic risk scores that measures the cumulative effects of a large number of individual SLE risk variants 99‐101 . Such risk scores can identify patients at increased risk for renal disorders, cardiovascular events and decreased survival 99,100 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic information may also be used to predict how severe the disease will be and identify patients that have an increased risk for certain organ manifestations. The genetic information can be leveraged by the use of polygenetic risk scores that measures the cumulative effects of a large number of individual SLE risk variants 99‐101 . Such risk scores can identify patients at increased risk for renal disorders, cardiovascular events and decreased survival 99,100 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to comorbidities with other IMIDs, there is great variability in the disease course followed by patients with SSc, since their treatment and prognosis in the long term is very heterogeneous. 20 Chen et al 17 developed a GRS based on a GWAS analysing patients with SLE with and without renal involvement, but this SLE nephritis-specific GRS did not outperform the SLE severity predictions achieved with a SLE GRS. Following a similar strategy, we generated two additional GRS based on the GWAS comparisons between clinical and serological subtypes in patients with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of significant contribution of sex to the GRS model was also reported previously in SLE. 17 Therefore, these counterintuitive results for a known SSc risk factor 19 were likely due to the selection of a sex-matched control population (online supplemental table 1), which would rule out the relevance of this parameter. The immune cell types included in the multivariate GRS were also concordant with the known aetiopathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this gene–environment interaction study of SLE risk, the largest conducted to date and the first, to our knowledge, to employ GWAS results rather than to investigate individual candidate polymorphisms, we created an updated, weighted GRS based on existing GRS studies of SLE (28,29), and tested for interactions between SLE genetic factors and smoking status in relation to their potential influence on SLE risk. We found that having a high wGRS and being a current or recent smoker were each individually strongly associated with SLE risk: each standard deviation increase in the wGRS more than doubled the risk of SLE, while current smokers and those who had recently quit smoking had an increased SLE risk of ~50% compared to never and more distant past smokers.…”
Section: Discussionmentioning
confidence: 99%